The Ultimate Remedium Principle in the Strategy of Returning and Recovering Corruption Crimes - Firdaus, Aras; Harve, Renhard; Simbolon, Bona Fernandez Martogitua (SASI, 2022)
Introduction: The problem of corruption is not new in a country. So that the application of the ultimum remedium principle in corruption crimes provides a deterrent effect for the perpetrators to recover assets from state losses. The ultimum remedium principle places criminal law as a last resort in realizing legal justice, legal certainty, and legal benefits.Purposes of the Research: This study aims to determine the principle of criminal law as a last resort (Ultimate Remedium) as an Effort in the Eradication of Corruption and how effective the ultimum remedium principle is in eradicating corruption.Methods of the Research: The research method used is normative research. Normative or doctrinal legal research is a legal research that puts the law as a building system of norms. The technique of data collection is done by literature study.Results of the Research: The study results show that the ultimum remedium principle is very effective if the punishment given to the perpetrators of corruption is in the form of hefty penalties to provide a deterrent effect and provide an example for the community not to do so. This study concludes that the ultimum remedium principle is the last step in achieving legal justice, legal certainty, and legal benefits.  So that an integral criminal justice system is carried out with a systemic approach with related policy arrangements in the field of structuring legal substance, legal structures or institutions, and legal culture.